Transnational families between Africa and Europe - (:unkn) unknown (My University, 2015)
This paper provides a descriptive and comparative analysis of transnational families with members located in A frica and E urope. It is thus far the only quantitative study, to our knowledge, that includes cross‐country comparisons and focuses on the A frican E uropean context. By comparing both countries of origin and destination, differences in family arrangements are found among G hana, S enegal, and the D emocratic R epublic of C ongo as well as within these groups depending on the E uropean destination countries. Findings show that dates of arrival and migrant legal status are most commonly associated with transnational family forms. Family and gender norms at origin, migration motivations, destination country family reunification and migration policies, and destination country characteristics related to language, employment opportunities, and educational system help to explain the differences found.
Keywords: African Research